Integrated systems analysis for coastal aquaculture - Zhao, Yanlai (University of Ottawa (Canada), 2004)
This paper presents a model for the evaluation of coastal zone sites in conjunction with supporting decision making on the use of potential sites for aquaculture as well as other site activities including commercial fisheries, and as reserves for natural resources. The decision support model captures site specific data in the form of a geographical information system that overlays selected geographical regions with natural resource dynamics, habitat, commercial activities including aquaculture, and influence plumes including toxicology. Descriptive data for selected regions including system overlays and interactions are then evaluated to provide input to a multicriteria analysis that positions decision makers with respect to the relative importance of resources, habitat, commercial activities, and influence plumes. The model compares alternative evaluations of selected regions among diverse users., as well as providing a group decision evaluation procedure to assist in coastal zonal governance decision makers such as the awarding of fish farm site applications. The model is applied to the coastal zone of Grand Manan Island, New Brunswick situated in the Bay of Fundy.
Keywords: Engineering, System Science.; Agriculture, Fisheries and Aquaculture.